ON DETERMINING THE D-STRUCTURE AND S-STRUCTURE OF WORLD LEADERS’ QUOTES - Muhamad Ahsanu (University of Muhammadiyah Purwokerto, 2013)
This article projects the syntactical aspects of world leaders' quotes via the X-bar theory. The reason why portraying the quotes utilizing the X-bar is due to the distinctiveness of the sentence patterns of the quotes themselves. By distinctiveness, world leaders tend to use simple sentence pattern in their creating their quotes and due to this simplicity the quote has endless impact and becomes easily chanted and widely known. For instance, the quote 'I have a dream' is very familiar to everyone's ears for partly it uses DP-VP-NP in the X-bar theory. This typicality is exposed through the primary research problems: what are the typical Dstructure configurations of the world leaders' quotes and how are the configurations transformed into their S-structures? Thus, this article focuses on discovering the underlying representations of the quotes of world leaders via the generative and transformational processes. The identified quotes are the internet-based data selected purposively. The article utilizes a descriptive and explanatory analysis. Keywords: D-structure, S-structure, world leaders’ quotes